1991
DOI: 10.1073/pnas.88.5.1711
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the terminal regions of hepatitis C viral RNA: identification of conserved sequences in the 5' untranslated region and poly(A) tails at the 3' end.

Abstract: We have determined the nucleotide sequence at the extreme 5' and 3' termini of the hepatitis C virus (HCV) genome. Our analyses ofthese sequences show (t) the nucleotide sequence in the 5' untranslated region is highly conserved among HCV isolates of widely varying geographical orign, (i) within this region, there are blocks of nucleotide sequence homology with pestiviruses but not with other viruses, (ii) the relative position of short open reading frames present in the same region of the HCV genome is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
204
1
3

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(214 citation statements)
references
References 24 publications
5
204
1
3
Order By: Relevance
“…HCV contains a positive-stranded RNA molecule of about 9400 nucleotides which contains a single large open reading frame encoding a viral polyprotein precursor of up to 3011 amino acids (aa) . The nucleotide and deduced aa sequences of the genomes of different isolates have shown that HCV is distantly related to flaviviruses and pestiviruses Miller & Purcell, 1990;Takeuchi et al, 1990;Kato et al, 1990;Takamizawa et al, 1991 ;Choo et al, 1991 ;Han et al, 1991). These characteristics, as well as the gene organization of HCV, are consistent with the theory that at least one of the causative agents of post-transfusion non-A, non-B hepatitis is a small enveloped virus, such as a togavirus or flavivirus (Bradley et al, 1983).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirsupporting
confidence: 67%
See 1 more Smart Citation
“…HCV contains a positive-stranded RNA molecule of about 9400 nucleotides which contains a single large open reading frame encoding a viral polyprotein precursor of up to 3011 amino acids (aa) . The nucleotide and deduced aa sequences of the genomes of different isolates have shown that HCV is distantly related to flaviviruses and pestiviruses Miller & Purcell, 1990;Takeuchi et al, 1990;Kato et al, 1990;Takamizawa et al, 1991 ;Choo et al, 1991 ;Han et al, 1991). These characteristics, as well as the gene organization of HCV, are consistent with the theory that at least one of the causative agents of post-transfusion non-A, non-B hepatitis is a small enveloped virus, such as a togavirus or flavivirus (Bradley et al, 1983).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirsupporting
confidence: 67%
“…Thus, the diameter of HCV particles estimated in this study was smaller than had been thought previously. However, the 5' structural gene region of HCV is much smaller than that of flaviviruses and is more like that of pestiviruses (Takeuchi et al, 1990;Han et al, 1991), which also have smaller diameters and relatively lower buoyant densities than flaviviruses (Mayr et al, 1967;Horzinek, 1973). Another explanation may be that particle diameter is altered by the treatment of virus samples for electron microscopy or the pretreatment of the filter to minimize the adsorption of virus to the membrane during filtration (Kamide et al, 1982).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirmentioning
confidence: 99%
“…Conversely, asymptomatic HCV carriers with normal serum ALT levels (P õ .01). E2/NS1 antibody titers were also lower 8 of the 13 patients with low viremia of õ10 6 prevalence was estimated to be very low at 10 to 17%…”
Section: Resultsmentioning
confidence: 96%
“…The putative organization of the HCV genome (ordered from the 5Ј-end) is as follows: the 5Ј-UTR; three or four structural proteins (core, E1, E2/p7); six nonstructural (NS) proteins (NS2, NS3, NS4A, NS4B, NS5A, NS5B); and the 3Ј-UTR. [5][6][7] However, the effects of these proteins on the functions of HCV-infected cells are not fully understood.…”
mentioning
confidence: 99%